Peran DPRD Lampung Selatan dalam Menunjang Sustainability Development Goals Pada Objek Wisata Di Lampung Selatan - Irawan, Bambang; Handayani, Agustia; Thahir, Andi (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
This research was conducted to determine the role of the South Lampung DPRD in supporting Sustainable Development Goals at tourist attractions in South Lampung. This research is classified as a qualitative research type with a case study design. Case studies are carried out for The aim is to investigate how these events occur systematically over a longer period of time. A case study is a type of qualitative research conducted in a specific context, referring to a particular program, activity, event, or group. The general goal of sustainable development or sustainable development goals (SDGs) is development to always improve the economic welfare of the community continuously without interruption, this development continues continuously to maintain the social life of the community, development that continues to maintain the quality of the environment and development in ensuring justice and continue to manage improving the quality of life from one generation to another. The Regional People's Representative Council (DPRD) is an integral part of regional government in the context of a unitary state. This is due to the absence of a special legislative body for the regional level in the unitary state structure. Therefore, the DPRD is integrated into the regional government structure.